APA Handbook of Multicultural Psychology, Vol. 1: Theory and Research. 2014
DOI: 10.1037/14189-011
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation research: Challenges, complexities, and possibilities.

Abstract: For immigrant children, as for adults, cultural change begins when they enter the new country; however, the process of acculturation for children is a more nuanced experience. Not having completedCopyright American Psychological Association. Not for further distribution.1 In this chapter, we use the term acculturation to refer to an immigrant's relationship to both heritage and host cultures as a bilinear process. We use the term enculturation to refer to the general process of cultural socialization that for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(86 citation statements)
references
References 135 publications
(194 reference statements)
4
73
0
1
Order By: Relevance
“…Ultimately, our study does not permit causal inference, and thus we cannot rule out the temporal ordering of variables. However, in light of all the findings and the larger literature, our study once more points to the importance of social contexts-namely, ecological diversity, levels of prejudice and discrimination, and sociocultural atmosphere/ climate (e.g., prominent values and attitudes held in a given geographical area; Alamilla et al, 2016;Birman & Simon, 2014;Christ et al, 2013)-in understanding the role of acculturation on the perceived racism and mental health link in this population (Nguyen, 2006). Thus, not only are more contextual studies of acculturation/enculturation and perceived racism needed, but longitudinal studies are also needed to help elucidate the temporal ordering of the relationship between acculturation/enculturation and perceived racism.…”
Section: Moderating Effects Of Acculturation/enculturation On Perceivmentioning
confidence: 83%
See 2 more Smart Citations
“…Ultimately, our study does not permit causal inference, and thus we cannot rule out the temporal ordering of variables. However, in light of all the findings and the larger literature, our study once more points to the importance of social contexts-namely, ecological diversity, levels of prejudice and discrimination, and sociocultural atmosphere/ climate (e.g., prominent values and attitudes held in a given geographical area; Alamilla et al, 2016;Birman & Simon, 2014;Christ et al, 2013)-in understanding the role of acculturation on the perceived racism and mental health link in this population (Nguyen, 2006). Thus, not only are more contextual studies of acculturation/enculturation and perceived racism needed, but longitudinal studies are also needed to help elucidate the temporal ordering of the relationship between acculturation/enculturation and perceived racism.…”
Section: Moderating Effects Of Acculturation/enculturation On Perceivmentioning
confidence: 83%
“…Our findings for values acculturation and values enculturation implicate ethnocultural difficulties associated with being Asian American in a predominantly European American institution/social context. Moreover, the findings highlight the importance of the broader social context in understanding acculturation, enculturation, and mental health (Berry, 2006;Birman & Simon, 2014;Lara et al, 2005;Nguyen 2006). Our results point to much needed research on how acculturation and enculturation are influenced by and interact with one's social environment-and are consistent with acculturation theory.…”
Section: Acculturation Enculturation and Psychological Symptomsmentioning
confidence: 86%
See 1 more Smart Citation
“…& Berry, 2010). Psychological acculturation has been conceptualized as a process that involves multiple dimensions involving language, behavior, and identity (Birman & Simon, 2014). Identity development is of critical importance in adolescence, shaping various aspects of life such as emotional, relational, and academic trajectories (Erikson, 1964;Pahl & Way, 2006).…”
mentioning
confidence: 99%
“…Qualitative and mixed-methods studies have identified ethnic identity as related to thriving in Latina/o college students (Morgan Consoli et al, 2014Consoli et al, , 2015. Some scholars have stated that, across ethnic groups, ethnic discrimination results in an increased ethnic identity (Birman & Simon, 2014). However, previous research examining the role of ethnic identity in the relationship between ethnic discrimination and mental health has reported mixed findings, with some work indicating that a strong sense of belonging serves a protective function and other work stipulating that it exacerbates mental health problems (Torres & Ong, 2010).…”
Section: Cultural Identitymentioning
confidence: 99%